IMPLEMENTATION OF THE JUDICIAL SYSTEM INVOLVING AMICUS CURIAE AS THE JUDGE'S CONSIDERATION IN PROVIDING DECISIONS IN EFFECTING THE PRINCIPLE OF PROPORTIONALITY - Ketaren, Elfani Br (NOMOI Law Review, 2023)
Amicus curiae is a legal concept where a third party feels interested in a case by providing their legal opinion to the court. This interest is only in the form of providing an opinion in the realm of court and is only material for consideration by the Judge, thus allowing every citizen to provide their views and opinions on a case, however the practice of amicus curiae is not yet clearly regulated in Indonesian positive law.This type of research and approach is normative research using a normative juridical legal research approach. Based on the results of research that the position of the amicus curiae in the judicial system in Indonesia is a matter for consideration by the judge in determining a decision in the judiciary, until now, there is no clear legal regulation regarding the concrete involvement of the amicus curiae in the trial process of criminal cases in Indonesia . Legal regulations regarding amicus curiae are not merely to assist judges in obtaining information on factual truths, but can promote proportionality between the judicial system in enforcing law enforcement based on a balance between the interests of society, the interests of the state, the interests of the perpetrator and the interests of the victim.